STUDENTS’ PERCEPTION OF GROUP WORK AND KNOWLEDGE BUILDING IN AN ECONOMICS UNIT (Proceedings of the International Conference on Education, 2017)
The purpose of this study is to examine students’ perception of group work and knowledge building in an economics unit. Even though economics is a required subject for most business courses in higher education, past studies have shown that students perceived economic concepts as too abstract to understand and irrelevant to the real world. A qualitative research approach was chosen, using semi-structured face-to-face focus groups and/or individual interviews with forty-six business students who voluntarily participated in this study. The research results revealed that students have either a positive or negative perception of group work and knowledge building experience. Furthermore, this study found out that students who work in groups are able to demonstrate their ability in making economic concepts relevant by connecting the concepts to the real world if there is an on-going collaborative effort among team members. Guidance from the lecturer and team members could support some students particularly those who came from high school to tertiary learning, and where this is their first exposure to group work that deals with the complexities of real world events. The results presented may facilitate improvements in group work and increase the likelihood of knowledge building in economics subjects.
Keywords: Group Work; Knowledge Building; Collaborative Learning; Economics